Evaluasi Sistem Pemesanan Jasa Make Up Artist Menggunakan Metode Rapid Application Development dan PIECES - Wawan Kurniawan; Jhon Cavlin Jovin (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2026)
This study aims to evaluate a Make Up Artist service booking system using the Rapid Application Development (RAD) method with PIECES evaluation. The evaluation was conducted using a pre-test and post-test approach to compare system conditions before and after implementation. The PIECES method was applied to measure system quality based on six dimensions: performance, information, economy, control, efficiency, and service. The results indicate that the average system quality score increased from 54% before implementation to 84% after implementation, showing an improvement of 30%. These findings demonstrate that the implemented system significantly improves service quality, operational efficiency, and customer satisfaction. Therefore, the combination of RAD and PIECES evaluation is effective in enhancing the quality of Make Up Artist service booking systems.